Erosion and Deposition induced Land Use Changes: A Geospatial Analysis on Sangu River, Bangladesh (Chittagong University Journal of Biological Sciences, 2024)
The study attempts to measure the eroded and deposited area of the Sangu River to understand the impacts of river systems on land use changes. Landsat photos of the last 28 years of the Sangu River floodplain (Anowara and Banshkhali Upazila of Chattogram) were analyzed at 5-year intervals using GIS and remote sensing techniques. ArcGIS 10.8v and ERDAS IMAGINE 2015 were used for the analysis. Results show that the total area that has been eroded and deposited during the past 28 years is 7070.70 ha and 437.87 ha, respectively. Moreover, a substantial portion of the deposited land has already been transformed for commercial uses such as shrimp cultivation which might deteriorate the soil fertility in the future and could exacerbate the salinity aggression in this area. It is expected that the study will contribute in the optimization and management of the floodplain which is crucial for the safety and welfare of the communities.Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 8-18, 2024